Impact of coronavirus 2019 infection on the kidneys in Assiut governorate - Eman A Abd El-Gaber; Eglal M Kenawy; Waleed S EL-Nasser; Ebtisam S Hassanin (Wolters Kluwer Medknow Publications, 2021)
Background and aim Several previous studies on coronavirus disease 2019 (COVID-19) cases reported that impairment of organs, that is, the liver, heart, and the kidneys, other than the lung can occur. This study aimed to evaluate the impact of COVID-19 infection on the kidneys. Patients and methods The current study was conducted as a retrospective and prospective study, where two samples of adult inpatients (aged >18 years) were recruited. The study was carried out in the period from April to June 2020 (the first wave) and from December 2020 to February 2021 (the second wave). Results A total of 1065 COVID-19 confirmed patients were admitted to the two Asyut governorate quarantine hospitals by the end of the study period (first wave n=525 and second wave n=540 patients). According to renal function parameter results, kidney injury was reported in 57.5% (n=302) of the patients in the first wave and in 58.7% (n=317) of cases in the second wave. On follow-up, only a small proportion (<10%) of patients had improvement in the kidney function parameters. Conclusion About half of the confirmed COVID-19 patients admitted to the quarantine hospitals at Asyut Governorate had kidney injury, which persisted after treatment and less than 10% showed improvement on treatment with no significant effect on the mortality rate of the patients.